2020
DOI: 10.3390/ma13020309
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Thermal Properties of Modified Cu2O/Polypropylene (PP) Composite

Abstract: A uniform, monodispersed superfine cuprous oxide (Cu2O) sphere with a mean diameter of 850 nm has been synthesized by solution reduction. The study reported the synthesis and thermal properties of Cu2O/PP composites for the first time. The surface modification of the superfine Cu2O sphere was carried out by using a silane coupling agent KH-570. Fourier-transform infrared (FTIR) spectroscopy and the thermogravimetric analysis (TGA) curve revealed that the Cu2O had been successfully modified by silane coupling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The effect produced by copper on the stability of the polymeric matrix of iPP is not clear, reports indicate that the stability is negatively and positively affected, generally the positive effects are observed when using NPs of large size (850 nm) and CuO NPs [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect produced by copper on the stability of the polymeric matrix of iPP is not clear, reports indicate that the stability is negatively and positively affected, generally the positive effects are observed when using NPs of large size (850 nm) and CuO NPs [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Yanying Jiang et al observed a rise of 3 °C in the T c of iPP/CuO composites. They attributed this increase to the low efficiency of CuONPs as nucleating agents [ 28 ]. The greater increase in T c observed in the iPP/CuNPs composites suggests that the CuNPs have a greater nucleating effect on the crystallization rate of iPP compared to CuONPs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dispersion of the fillers can be improved via surface modification of the inorganic particles by increasing the surface tension and roughness of the particles or changing their surface chemical properties to improve the adhesion between the particles and the matrix [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. For example, Yang et al [ 21 ] modified nanostructured calcium carbonate (nano-CaCO 3 ) with γ-(2,3-epoxypropyloxy)propyltrimethoxysilane (KH560), 3-(methacryloxy)propyltrimethoxysilane (KH570), or isopropyl dioleoyloxy(dioctyl phosphate acyloxy) titanate.…”
Section: Introductionmentioning
confidence: 99%